Pengaruh karakteristik pekerjaan dan kompetensi terhadap kinerja melalui komitmen organisasional - Aminin, Nur; Tristiana Rijanti (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The problems in this study are how job characteristics affect employee performance, how competence affects employee performance, how job characteristics affect organizational commitment, how competence affects organizational commitment, how organizational commitment affects employee performance, how is the role of organizational commitment in mediating the influence job characteristics on employee performance and how the role of organizational commitment in mediating the influence of competence on employee performance. The sample taken in this study was the entire population, namely Kelurahan Employees in the Wiradesa Subdistrict, Pekalongan Regency totaling 112 employees. The analytical tools used are validity and reliability tests, descriptive statistics and regression analysis. The results of hypothesis testing show a positive and significant effect of job characteristics on performance, competence on performance and organizational commitment on performance, while job characteristics on organizational commitment show a negative and insignificant effect. Likewise, competence on organizational commitment shows an insignificant negative effect.